Peripheral inflammation and neurocognitive impairment: correlations, underlying mechanisms, and therapeutic implications - Tan, Siyou; Chen, Wenyan; Kong, Gaoyin; Wei, Lai; Xie, Yubo (Frontiers in Aging Neuroscience, 2023)
Cognitive impairments, such as learning and memory deficits, may occur in susceptible populations including the elderly and patients who are chronically ill or have experienced stressful events, including surgery, infection, and trauma. Accumulating lines of evidence suggested that peripheral inflammation featured by the recruitment of peripheral immune cells and the release of pro-inflammatory cytokines may be activated during aging and these conditions, participating in peripheral immune system-brain communication. Lots of progress has been achieved in deciphering the core bridging mechanism connecting peripheral inflammation and cognitive impairments, which may be helpful in developing early diagnosis, prognosis evaluation, and prevention methods based on peripheral blood circulation system sampling and intervention. In this review, we summarized the evolving evidence on the prevalence of peripheral inflammation-associated neurocognitive impairments and discussed the research advances in the underlying mechanisms. We also highlighted the prevention and treatment strategies against peripheral inflammation-associated cognitive dysfunction.